Bodies at risk: Ambiguous subjectivities in Arlington Park.A Beauvoirean perspective - Maria TANG (E-REA)
In the “book of repetition” that is Arlington Park, Rachel Cusk, I argue, runs the “risk of the feminine,” in ways that seem to rehearse the paradigm of sexual difference both raised and challenged by Beauvoir in The Second Sex. I start by looking at how the women of Arlington Park seem (to adopt the Beauvoirean terminology) mired in immanence and facticity, cut off from the transcendence that would confer subjectivity on them. Cusk’s endeavour in the novel probes the ambiguities of her female characters’ existences, which lead them paradoxically to choose that which oppresses them. This contradiction is the focus of Cusk’s “women’s writing,” which is less concerned with questions of “female identity” than with questions of action and choice that limit women’s freedom in ambiguous and contradictory fashions, producing an alienating split in their subjectivity. Ambiguity is at the heart of Arlington Park, where the female characters are cast as “bodies at risk,” all seeking new ways of relating to others which will neither immure them in, nor exclude them from, prevailing representations of femininity. Cusk’s women experience the specific risks associated with the ambiguously shared spaces of domesticity which embed the “other within” and require exposure, openness and generosity. Drawing on the recent revisionary work on Beauvoir by Fredrika Scarth in particular, this paper examines the ways in which the lived experience of womanhood is dramatized in the novel as a kind of risk that is not only physical but also ontological. It is a risk that Cusk’s novel figures as a truly creative act.